PHYSICAL ACTIVITY AND LIFE’S ESSENTIAL 7: A CROSS-SECTIONAL STUDY - Carvalho, Melissa Dias; Oliveira, Mateus Augusto de; Machado, Guilherme Andrade; Costa, Ríllary Neto; Filho, Francisco Ronaldo Caliman; Viana, Fernando Pires; Langsdorff-Serafim, João Paulo; Sousa, Wanderson Sales de; Silva, Pedro Henrique de Almeida (CIPEEX, 2025)
Physical activity is important for maintaining cardiovascular health (CVH), particularly in adult women. Factors such as a sedentary lifestyle and obesity increase the risk of cardiovascular disease (CVD) in this population. The objective of this study was to compare physical activity level (PAL) with CVH of active and sedentary women. This was a cross-sectional study conducted with female employees at a higher education institution. The sample consisted of 51 women, recruited by invitation. The project was approved by the Ethics and Research Committee of the Evangelical University of Goiás under number 4,512,382/2021. CVH was assessed using seven metrics (PAL, smoking status, body mass index (BMI), diet, systemic blood pressure (SBP), fasting glucose (FBG), and total cholesterol (TC)) recommended by the American Heart Association (AHA) life's essential 7 guideline. PAL was assessed using the International Physical Activity Questionnaire (IPAQ-short version). Diet was assessed using the Mediterranean Diet questionnaire. Smoking status was self-reported. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were measured using a semi-automatic device, and blood samples were collected for FBG and TC analysis. Data were expressed using descriptive statistics. Student's t-test and Mann-Whitney test were used to compare groups (active and sedentary women). Sedentary women had higher DBP (p <0.001) and lower CVD scores (p <0.001). In conclusion, a good PAL contributes to reducing risk factors associated with CVD in adult women.